Unique layered double hydroxide morphologies using reverse microemulsion synthesis. - Hu, G; O'Hare, D (2005)
We report the first controlled synthesis of a layered double hydroxide (LDH) in a water-in-oil reverse microemulsion system. This synthesis of Mg2Al-LDHs was carried out in the reverse microemulsion of NaDDS (sodium dodecyl sulfate)-water-isooctane with water/surfactant molar ratio = 24. This enables us to obtain nanometer sized LDH platelets typically with a 40-50 nm diameter and 10 nm thickness. Further modification of the reverse microemulsion using triblock copolymers during crystallization allowed us to express different growth orientations of the LDH structure. These data show that the aspect ratio of LDHs can be flexibly adjusted over a wide range.